Anistia de 1979 e transição política: dos projetos e campanhas à luta por justiça e reparação às vítimas sergipanas - Vieira, Cleidson Carlos Santos (2015)
This research was aimed at discussing the projects around the 1979 Amnesty Law, as well as the mobilization of society for which this Act was "broad, general and unrestricted", and how the adoption of this law influenced the repair process the victims. In this regard it is important to bring out the formulations of political organizations, such as the Brazilian Committee for Amnesty (CBA), and the Movement for Amnesty Female (MFPA), and tells the story of its operations in the state of Sergipe. What were their slogans? What was his amnesty project? What perspective prevailed in the dispute that was fought during the transition period of the dictatorship? The political interests of the dominant social subjects in the law approving context gave a forgetting of character and appeasement to the process that continues repercussions. Ie approval of this law influenced the setting of institutional logic galgada unpunished and will play, as regards compensation policies for victims of the dictatorship, strongly still present today. It fell also discuss the role of family and Sergipe victims in the fight for truth and justice, both in the context of adoption of the Amnesty Law, and in effect this theme in society.